Economic Feasibility Study Implementation of Big Data Technology in Strategic Decision Making in the Financial Sector - Efriyani Sumastuti (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study aims to evaluate the economic feasibility of implementing big data technology in strategic decision-making in the financial sector in Indonesia. The research used a survey method of financial institutions such as commercial banks, insurance companies, securities companies, financing institutions, and fintechs. The results showed that 68% of financial institutions have adequate technology readiness, but there are still infrastructure challenges in some areas. The majority of respondents (85%) recognize the great benefits of big data, particularly in improving the effectiveness and speed of decision-making. However, 40% of financial institutions are still concerned about data security and privacy risks, indicating the need for increased investment in cybersecurity. Most respondents (72%) reported a positive impact on profitability and operational efficiency after implementing big data. The study concludes that while the initial cost of implementing this technology is significant, the long-term benefits in terms of improved competitiveness and financial performance of financial institutions are substantial. Therefore, the implementation of big data in the financial sector in Indonesia is considered economically viable, provided it is complemented by a robust risk mitigation strategy and compliance with data protection regulations.